KOMBINASI TEPUNG TERIGU DAN TEPUNG TAPIOKA TERHADAP DAYA KEMBANG DAN SIFAT ORGANOLEPTIK KERUPUK TERUBUK (Saccharum edule Hasskarl) - Ramadhani Chaniago; Darni Lamusu; Lutfi Samaduri (Jurnal Pengolahan Pangan, 2019)
Terubuk processing techniques are still simple, such as processed into vegetables. Therefore, it is necessary to diversify food, namely making crackers in powder. Crackers are a type of small food that undergoes volume development forming a product that is porous and has a low density during the frying process. This study aims to determine the growth and organoleptic properties of crackers made from powder (Saccharum edule Hasskarl). this study was designed using a Completely Randomized Design (CRD) arranged with 1 factor, namely: A1 = 100 gram wheat flour + 200 gram tapioca flour + 100 gram flour; A2 = 150 gram wheat flour + 100 gram tapioca flour + 150 gram powder; A3 = 100 gram flour + 150 gram tapioca flour + 100 gram powder. Based on the organoleptic test results showed that: The best flower power is shown in treatment A1 (100 gram wheat flour + 200 gram tapioca flour + 100 gram flour) which is 75.58%. The panelist's assessment or organoleptic test of the combination of wheat flour, tapioca tapung and terubuk gave no significant effect on color, taste and texture and gave a real influence on the aroma of crackers made in powder. The best treatment based on the panelist's assessment is treatment (A2) Wheat flour 150 grams + Tapioca flour 100 grams + Powdered 150 grams. Where these crackers have a color value of 3.75 rounded to 4 (likes); the aroma value of 3.93 is rounded to 4 (likes); the flavor value of 3.57 is rounded to 4 (likes) and the texture value is 3.75 (likes).